Improving chronic disease monitoring in resource limited settings: simulation and economic evaluation approaches - Mukonda, Elton (Department of Public Health and Family Medicine, 2025)
Introduction: Chronic diseases are persistent long-term conditions causing significant premature mortality, functional impairment, and disability, often needing ongoing care and support. Management of these long-term conditions is an important, but costly element of health care which relies on clinical practice guidelines (CPGs) to standardise the provision of care. In low-and-middle-income countries (LMICs), where healthcare infrastructure and financial resources are often insufficient, CPGs need to strike a careful balance between evidence-based recommendations and the pragmatic feasibility of implementation. However, the scarcity of locally designed guidelines in LMICs has led to a reliance on guidelines from High-Income Countries (HICs) despite the substantial contextual differences between the origin of guidelines and their intended application settings. Within this terrain, there is a particular need for evidence around the impact of adhering to the adopted guidelines and exploring opportunities for improvement. A crucial, yet understudied component of CPGs that could particularly benefit from such scrutiny and evaluation is monitoring. The aim of this thesis is to generate evidence on the suitability of current guidelines, and potentially identify alternative strategies for monitoring chronic diseases, with a specific emphasis on Type-2 Diabetes Mellitus (T2D), using South Africa as a case study. Methods: A mixed-methods approach including a literature review, analytic studies, and a formal economic evaluation, was used to address the aim of the thesis. A comparative analysis of monitoring guidelines from LMIC and HIC settings was conducted to describe how monitoring guidelines for three chronic diseases: HIV/AIDS, hypertension, and T2D, are developed, summarising both the evidence and the strength of evidence used to develop the recommendations. The analytical study then utilised individual-level data on adults living with T2D in the Western and Northern Cape, South Africa to examine the relationship between adherence to current HbA1c monitoring guidelines and the achievement of glycaemic control targets, as well as longitudinal changes in HbA1c. Two properties, the retest interval, and the monitoring adherence rate were calculated and associations were derived using linear mixed effects modelling, and multistate modelling. An in-depth review of model-based studies on T2D populations in LMICs was then conducted to identify methodologies available for extrapolating insights from short-term empirical studies and projecting costs and health benefits over an individual's lifetime. Finally, a Markov simulation model was developed using methodologies identified in the afore-mentioned review to extend the short-term findings from the analytical study and assess the long-term effectiveness and cost-effectiveness of different HbA1c monitoring strategies with the aim of identifying the optimal HbA1c monitoring in patients with T2D. HbA1c monitoring strategies (three-monthly, four-monthly, six-monthly, and annual tests) were evaluated with respect to the incremental cost-effectiveness ratio (ICER) assessing each comparator against a less costly undominated alternative. Findings: Findings from the comparative analysis highlight how monitoring recommendations in LMIC guidelines closely resemble those in HIC guidelines with little to no consideration made for factors like genomics, resource availability, or socioeconomic context. Furthermore, the recommendations for monitoring HbA1c in T2D management and blood pressure in hypertension are based on expert opinion and clinical consensus. Findings from the analytical study reveal that a retest interval between 2-4 months is associated with the greatest reduction in HbA1c, while individuals with low adherence to the monitoring guidelines were the least likely to achieve glycaemic control in one year. Moreover, patients with low monitoring adherence had higher mean HbA1c levels compared to patients with moderate or high monitoring adherence. The literature review highlights an increase in the number of modelling studies investigating the long-term impact of interventions for T2D in LMICs, with most of these studies being from Asia. In addition, there is no consensus on the most appropriate modelling approach, as appropriateness is dependent on a variety of factors, including the study objective and data availability. However, a widely used approach is Markov modelling where the full spectrum of disease manifestations is characterized by mutually exclusive health states, and changes in health status over time are captured through transition probabilities between these states. Findings from the cost effectiveness analysis suggest annual and lifetime costs of managing diabetes increased with HbA1c monitoring, while increased monitoring provides higher quality-adjusted life years (QALYs) and Life Years. The ICER for six-monthly vs annual monitoring was cost-effective (USD 2,322.37 per QALY gained), whereas the ICER of moving from six-monthly to three-monthly monitoring was not cost-effective(USD 6,437.79 per QALY gained). The ICER for four-monthly vs six-monthly monitoring was extended dominated. The sensitivity analysis showed that the ICERs were most sensitive to health utilisation rates. Conclusion: Findings from the analytical studies and economic evaluation presented in this thesis provide strong evidence on the impact of HbA1c monitoring on costs and health outcomes in a LMIC and can be used as supporting evidence for current HbA1c monitoring guidelines, which are based on expert opinion and clinical consensus. Improving chronic disease monitoring in LMICs ultimately requires adapting guidelines and recommendations to the local context. Evaluating the effectiveness and cost-effectiveness of adopted CPG recommendations in LMICs is the first step to ensuring promotion of evidence-based, equitable healthcare practices.